2011
DOI: 10.1021/ol200740r
|View full text |Cite
|
Sign up to set email alerts
|

Ti(O-i-Pr)4/Me3SiCl/Mg-Mediated Reductive Cleavage of Sulfonamides and Sulfonates to Amines and Alcohols

Abstract: A low-valent titanium generated in situ from Ti(O-i-Pr)(4), Me(3)SiCl, and Mg powder in THF reacted with aryl- and alkyl-sulfonamides of aryl and alkyl amines in a reductive N-S/S-O/S-C bond cleaving pathway to provide the corresponding amines and hydrocarbons (and thiols) derived from the sulfonyl moiety. The reagent could also cleave sulfonates to the corresponding alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…The tosyl groups of (M)-2 were initially removed according to the reported procedure 21 to give spirobiquinoline (M)-5 22 (Scheme 2). Diphosphine (M)-6 was successfully synthesized by the treatment of secondary amine 5 with n-BuLi followed by the addition of Ph 2 PCl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tosyl groups of (M)-2 were initially removed according to the reported procedure 21 to give spirobiquinoline (M)-5 22 (Scheme 2). Diphosphine (M)-6 was successfully synthesized by the treatment of secondary amine 5 with n-BuLi followed by the addition of Ph 2 PCl.…”
Section: Resultsmentioning
confidence: 99%
“…. 21 To a mixture of (M)-2 (55.9 mg, 0.100 mmol) and Mg powder (24.3 mg, 1.00 mmol) in THF (0.5 mL) were added Ti(O-i-Pr) 4 (56.8 mg, 0.200 mmol) and Me 3 SiCl (32.8 mg, 0.302 mmol). The reaction mixture was allowed to stir at 50 °C for 24 h. After being cooled to room temperature, to the mixture were added sat.…”
Section: Nn'-(22-bis(2-bromobenzyl)propane-13-diyl)bis(4-methylbenmentioning
confidence: 99%
“…[17] Subsequent treatment of the resulting 2-amino-2'-methoxy-1,1'-binaphthyl with boron tribromide gave (R)-NOBIN without any loss of enantiomeric purity. For example, the benzenesulfonyl group of (R)-1 a was removed by treatment with a low-valent titanium reagent, which was generated in situ from titanium(IV) isopropoxide, trimethylsilyl chloride, and magnesium powder.…”
Section: Seiji Shirakawa Xiangfei Wu and Keiji Maruoka*mentioning
confidence: 99%
“…Encouraged by this, a detailed optimization study was first done with different phosphoric acid catalysts. Inspired by a recent review on Hantzsch esters as the hydride sources for transfer hydrogenations, [16] we screened different Hantzsch esters (Table 1, entries [15][16][17] and found that HEH3 gave rise to a better result (S = 303) with 98 % ee of the recovered 1 a and 97 % ee of the product (Table 1, entry 16). It should be noted that the yield and ee of product 3 a was always excellent with different BINOLderived catalysts (Table 1, entries 2-6), even in the presence of the catalyst with phenyl group on the 3,3'-positions (Table 1, entry 3), while ee of the recovered 1 a varied.…”
mentioning
confidence: 99%
“…To demonstrate the utility of the current procedure, the bulky protecting groups of the resulting optically pure transfer hydrogenation product (S)-3 a and recovered starting material (R)-1 a [17] could be readily removed to produce (S)-BINAM and (R)-BINAM with moderate to high yields, and the enantiopurity can be completely retained (Scheme 3), which has been suggested to have wide applications as the effective asymmetric organocatalysis. [4,5] The optically pure product (up to 100 % ee) can be obtained after a single recrystallization process of the enantiomerically enriched (S)-BINAM from toluene.…”
mentioning
confidence: 99%